2021
DOI: 10.1021/acsomega.1c05379
|View full text |Cite
|
Sign up to set email alerts
|

Hydration of LiOH and LiCl─Near-Infrared Spectroscopic Analysis

Abstract: The hydration behavior of LiOH, LiOH·H2O, and LiCl was observed by near-infrared (NIR) spectroscopy. Anhydrous LiOH showed two absorption bands at 7340 and 7171 cm–1. These NIR bands were assigned to the first overtone of surface hydroxyls and interlayer hydroxyls of LiOH, respectively. LiOH·H2O showed two absorption bands at 7137 and 6970 cm–1. These NIR bands were assigned to the first overtone of interlayer hydroxyls and H2O molecules coordinated with Li+, respectively. The interlayer OH– and the coordinate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 78 publications
0
12
0
Order By: Relevance
“…These observations indicate that the hydrogen-bond network between Ca­(OH) 2 layers is more stable than Mg­(OH) 2 . This fact can be confirmed by the different dehydration temperatures of Mg­(OH) 2 and Ca­(OH) 2 to be approximately 370 and 430 °C, respectively. Furthermore, the absorption band at 4176 cm –1 was assigned to a combination of the librational mode of the HO–Ca–OH unit (560 cm –1 ) and the asymmetric stretching mode of OH (3640 cm –1 ). , As mentioned in previous studies, , the wavenumbers of fundamental vibration ( ) and the 1st overtone ( ) can be estimated by the eqs and where, ν̅ and χ̅ are the frequency (wavenumber) and anharmonic constant, respectively.…”
Section: Resultsmentioning
confidence: 56%
“…These observations indicate that the hydrogen-bond network between Ca­(OH) 2 layers is more stable than Mg­(OH) 2 . This fact can be confirmed by the different dehydration temperatures of Mg­(OH) 2 and Ca­(OH) 2 to be approximately 370 and 430 °C, respectively. Furthermore, the absorption band at 4176 cm –1 was assigned to a combination of the librational mode of the HO–Ca–OH unit (560 cm –1 ) and the asymmetric stretching mode of OH (3640 cm –1 ). , As mentioned in previous studies, , the wavenumbers of fundamental vibration ( ) and the 1st overtone ( ) can be estimated by the eqs and where, ν̅ and χ̅ are the frequency (wavenumber) and anharmonic constant, respectively.…”
Section: Resultsmentioning
confidence: 56%
“…Instead, in LiOH-10, NaOH-10, and KOH-10, peaks of Li 2 CO 3 , Na 2 CO 3 , and K 2 CO 3 were detected. It has been found that LiOH is carbonated within 6 h when exposed to air, based on a previous study 24) , and the basicity of NaOH and KOH is stronger than that of LiOH; LiOH, NaOH, and KOH might partially react with CO 2 in air during preparation, measurement, or storage. Namely, it is implied that alkali metal hydroxides probably exist in the sample with the addition of alkali metal hydroxides when carbonates based on the alkali metal hydroxides are detected in the sample in XRD measurements.…”
Section: -10mentioning
confidence: 86%
“…The NIR bands at 7360 and 7309 cm −1 are correlated to a fundamental vibration (ν OH ) at 3763 and 3737 cm −1 using the anharmonic constant trueχ¯ (2.064 × 10 −2 ), which was calculated from the hydroxyl groups of the SiO 2 surface. [ 55,56 ] The absorption band at approximately 3730 cm −1 was assigned to four types of hydroxyl groups on the MgO surface by Knözinger et al [ 15 ] and two other types by Chizallet et al [ 18 ] Furthermore, Mutch et al assigned the absorption bands at 3723 and 3760 cm −1 to two “free” surface hydroxyl groups located on the MgO(111) facet. [ 87 ] Based on this consideration, the isolated hydroxyl groups (7360 cm −1 ) of the MgO surface readily converted to the hydrogen‐bonded hydroxyl groups (7309 cm −1 ).…”
Section: Nir Spectroscopic Observation Of Hydration Process Of Mgo In...mentioning
confidence: 99%
“…[42,43,47,48] This advantage of NIR spectroscopy enables the observation of hydrated materials and aqueous solutions. [49][50][51][52][53][54][55][56] Further, NIR spectroscopy provides important information about the hydrogen-bond networks of OH, NH, and SH groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation